An Anthology of Short Stories - The Association of Nigerian Authors, Lagos Chapter (Nigeria, 2022)
Nest of Tales is a special anthology dedicated to honour two literary icons: Mabel Segun, winner of 1954 National Festival of Arts Literature Prize and founding member of the Association of Nigerian Authors; Mobolaji Adenubi, author of Splendid which won the 1995 all Africa Prize for literature... In Nest of Tales we find the voices of many award winning cum established writers, as well as young emerging talents.
Keywords: Anthology; Fiction; Short Stories